An Alternative Approach Using Circummandibular Wiring for Treatment of Dentoalveolar Fractures in Children: A Case Report. Issue 2 (June 2022) - Quinto, José Henrique Santana; Bachesk, Andressa Bolognesi; Nogueira, Lucas Costa; Filho, Liogi Iwaki
The prevalence of dentoalveolar injuries in children is approximately 25%, with falls from own height being one of the main etiologies. Diagnosis is based on the clinical evaluation associated with complementary imaging tests. The treatment of choice depends on the type of damage and structure affected. For alveolar process fractures, closed reduction and semi-rigid dental splinting for 4 to 6 weeks is generally satisfactory. However, some cases, such as severe segmental fractures, require open treatment to ensure adequate reduction and stabilization of the displaced alveolar segment, which is usually achieved by titanium miniplates and screws. Nevertheless, there are situations where this type of fixation is not possible, requiring alternative methods. Therefore, this article describes a surgical technique performed by open reduction, associating semi-rigid dental splint and circummandibular wiring in pediatric patient diagnosed with dentoalveolar fracture through clinical examination (with bone fracture displacement) and tomography. The technique promoted a good prognostic to the patient, proving to be a viable alternative for treating dentoalveolar fractures.